Valuing Banyumas Cultural Heritage Tourism: A Comparative Analysis in Support of SDG’s 11 for Sustainable Cities and Communities - Suharno Suharno; Aziz Ahmad Abdul; Lestari Unik; Eltayeb Elfaki Khalid (E3S Web of Conferences)
The study of the economic valuation of cultural heritage tourism has a long history and has gained renewed interest in recent years. This paper poses a methodological challenge in using alternative scales to monetary ranges for cultural heritage valuation. A famous Banyumas cultural tourism site is taken as a case study, and the site's utility is estimated through the method of travel cost (monetary value) and time spent visiting the site (non-monetary scale). According to consumption theory, this study finds an inverse relationship between the two scales and demand intensity. While the monetary approach mainly reflects the cost of accessing cultural heritage tourism – ceteris paribus preference– the time spent approach shows that those who invest more time in the visit are fanatics, avid enthusiasts, fascinated visitors, engagement visitors, and educated adults. These results provide more efficient policy implications in cultural tourism management and market valuation. This aligns with Sustainable Development Goal (SDG) 11's objectives, which encourage making cities and human settlements inclusive, safe, resilient, and sustainable. By evaluating cultural heritage through monetary and non-monetary methods, this study supports the development of tourism policies that enhance visitor satisfaction and prioritise the sustainable management and preservation of cultural sites for future generations.